Trends in GP prescribing of psychotropic medications among young patients aged 16-24 years: A case study analysis - Brijnath, Bianca; Xia, T.; Turner, L.; Mazza, D. (BioMed Central Ltd., 2017)
Background: Current clinical guidelines recommend non-pharmacological interventions as first-line treatments for young patients aged 16-24 years with a mental health condition (MHC). However, several studies have noted increasing trends in psychotropic prescribing for this age group, especially in antidepressant prescribing. In Australia, the vast majority of psychotropic medications prescribed to young people come from the general practice setting. To assess whether Australian General Practitioners (GPs) are prescribing in accordance with clinical guideline recommendations, this study examined trends in GP prescribing of psychotropic medications to young patients aged 16-24 years. Methods: We performed a retrospective analysis of routine general practice data from 9112 patients aged 16-24 years with a MHC. Data were extracted from the Melbourne East Monash General Practice Database from 1/01/2009 to 31/12/2014. The main outcome measures included the number of consultations for patients with MHCs, psychotropic prescribing by GPs, and patient characteristics associated with the likelihood of being prescribed a psychotropic. Results: In total, 9112 out of a total of 77,466 young patients were identified as having a MHC in this study, and 11,934 psychotropic prescriptions were provided to 3967 (43.5%) of them over the study period. Antidepressants accounted for 81.4% of total psychotropic prescriptions, followed by anxiolytics (9.6%) and antipsychotics (9.0%). The number of prescriptions issued to individuals with MHCs increased over time. Women and patients aged 21-24 years had higher incidence rates for prescription than men and those aged 16-17 (IRR: 1.15, 95% CI 1.08-1.22, IRR: 1.93, 95% CI 1.750-2.11). Conclusions: Our findings demonstrate an increasing trend in GP prescribing of psychotropics to young people over the study period with higher levels of prescribing to women and those 21-24 years of age. Although GP prescribing corresponded with guideline recommendations on the whole, there were discrepancies between GP's antidepressant prescribing and guideline recommendations, reasons for which were unclear. Research is needed to investigate GPs decision-making processes underlying their prescribing, to target interventions to improve existing data in GP records to improve management, and to identify areas of further training if needed to facilitate greater concordance between clinical practice and guideline recommendations.